Habituation of Sipakainge Values In Bugis Local Wisdom: A Sustainable Strategy For Preserving Marine Tourism In The City of Parepare - Makkulau Wahyu Rio; Wirani Aisiyah Anwar; Nur Isma Padila (Politeknik Pariwisata Makassar, 2024)
Marine tourism in Parepare, such as Paputo Beach, Mattirotasi, Senggol, Lumpue, Cempae, Salo Karajae, and Tonrangeng, despite being popular tourist destinations, still faces waste pollution issues that disrupt the natural beauty and environmental sustainability. This is due to the community's low awareness of the importance of responsible waste management. This highlights the significance of the Sipakainge value in Bugis local wisdom as a sustainable effort to preserve marine tourism by involving community participation in maintaining the balance between resource utilization and environmental preservation. The method used in this study is a literature review by examining various literatures related to Bugis local wisdom, particularly the Sipakainge value, and the concept of marine tourism preservation. The data sources include books, journal articles, news reports, and relevant government reports from Parepare City. The data is then analyzed using content analysis techniques, focusing on how the Sipakainge concept can be applied as an environmental preservation strategy. The research findings show that the Sipakainge value, which contains the meaning of mutual reminders in solidarity, is an ethical and moral principle that has long been the foundation of Bugis social life. In the context of marine tourism preservation, this value becomes a key factor in maintaining the sustainability of coastal ecosystems. The Sipakainge value has strong relevance in supporting efforts to preserve marine tourism in Parepare City. It plays a role in encouraging the community to protect the coastal environment by strengthening collective awareness and social responsibility. This practice is reflected in Bugis traditions that respect the balance between resource utilization and environmental conservation. These values can be applied in managing marine tourism through environmentally friendly approaches and involving active participation from the local community. By instilling these values into tourism management practices, Parepare City can develop a tourism sector that not only benefits economically but also contributes to environmental preservation and long-term sustainability.